Residential Architecture of Margilan City (Eurasian Research Bulletin, 2022)
Residential architecture of Margilan city the relevance of the topic is that our homeland Our country, which has amazed many people with its high culture, science and architectural monuments, is turning into a modern tourist centre with the honour of independence. To repair historical monuments, sacred sites, mosques, madrasas, historical parks and other unique historical monuments in the territory of our republic without damaging their historical value, beautify them, introduce them to the world, give them a new and modern look with all conditions for the population. creation of residential projects, prevention of gross violations of the existing urban planning legislation, urban planning standards and regulations in the reconstruction and beautification of settlements, construction of production, and social and engineeringtransport infrastructure facilities, is one of the important problems facing the construction industry.